(untitled) (Economics and region, 2019)
Most of countries include Indonesia are facing threats especially radicalism. Many effort that is done by global radical group to spread their action such as spreading the radicalism via internet. Global radical group in Indonesia assigns the students as their target. This is a real problem that must be addressed seriously by Government of Indonesia and need the support from the educational institution to contra the radicalization. Educational institution could contribute of contra-radicalization activities through the teaching and learning process or educational curriculum and also by community service activities. The Alkhairaat Foundation is one of influential foundation in the Central Sulawesi Province, Indonesia, that has educational institution on the form of public school, islamic school, and university that are located on Sulawesi, Maluku, and Papua. From the research conducted by qualitative methods, the result shown that Alkhairaat had implemented contra-radicalization activities by contra-grienvances, contra-ideology, and contra-mobilization. Generally, the activities had carried out in the community through da’wah. As well as especially for contra-radicalization carried out through character education by requiring the implementation of curriculum to Alkhairaat which is made by PB Alkhairaat and must be applied by all of the organization under PB Alkhairaat. Implementation of contra-radicalization by Alkhairaat has succeeded in preventing radicalization in its cadre by implementing a local content curriculum (Muatan Lokal/Mulok) of Alkhairaat in the public school, islamis school, boarding school, and university. In line with the efforts of Government of Indonesia to developing character building on curriculum to educational institution so the curriculum of Alkhairaat could be a model for making character building on curriculum as an effort to contra-radicalization. This model could be implemented nationally and globally over the world.